Access to advanced healthcare services and its associated factors among patients with cervical cancer in Addis Ababa, Ethiopia - Shimels, Tariku; Gashawbeza, Biruck; Gedif Fenta, Teferi (Frontiers in Oncology, 2024)
This study aimed to assess the extent of access to healthcare services, perception and associated factors among patients with cervical cancer in Addis Ababa, Ethiopia. A facility-based cross-sectional study was conducted from 01 July through 30 August 2023 at two tertiary hospitals. Cases with histopathologic and clinical confirmation of cervical cancer were enrolled using a consecutive sampling technique. Data was collected through a validated questionnaire administered by interviewers using the KoboCollect application. Subsequently, the collected data underwent analysis using Statistical Sciences for Social Sciences (SPSS) version 26.0. Bivariable and multivariable regression models were performed at p≤0.2 and p<0.05 statistical significance, respectively. A total of 391 patients were enrolled in the study. Health facilities were accessible for obtaining general medical services (56.5%), drugs (57.3%), laboratory diagnosis services (57.0%), imaging diagnosis services (56.8%), and radiotherapy services (55.8%) of the patients. Cost of services was affordable only in 11.5% of the cases. Essential anticancer medicines were out of stock for 229 (58.6%) of the patients during the past three months. About two-thirds of the patients have a good perception of access to healthcare services. In multivariable binary logistic regression, admission to the inpatient (AOR: 0.2, 95% CI: 0.06-0.67), joblessness (AOR: 0.19, 95% CI: 0.08-0.46), lower level of income to the extreme poverty line (3567ETB)(64.9 USD) (AOR: 0.19, 95% CI: 0.10-0.35), no CBHI coverage (AOR: 4.16, 95% CI: 1.76-9.85), having social support (AOR: 3.80; 95% CI: 1.96-7.41), and poor dietary practice (AOR: 2.36, 95% CI: 1.28-4.35) were found to have a statistically significant association with perceived good access to healthcare services. Only close to a half of the patients with cervical cancer, in Addis Ababa, have adequate access to healthcare services. Nearly two-thirds of the patients reported perceived good access to the services. Many factors were found to show a statistically significant association with patients’ perceived access to healthcare services.